Possibilities for an international assessment in geography. Issue 1 (2nd January 2017) - Lane, Rod; Bourke, Terri
ABSTRACT: A recent editorial in International Research in Geographical and Environmental Education (IRGEE) highlighted an opportunity for the inclusion of geography as a subject in the Trends in International Mathematics and Science Study (TIMSS) tests. At present, TIMSS tests only encompass mathematics and physical sciences. The IRGEE editors encouraged geography educators to take the initiative and be proactive for a TIMSS international assessment in geography to become a reality. This paper reports on a research project to identify the perceptions of the global geography education community on the advantages and challenges of initiating and implementing such tests. The authors highlight a number of consistencies and tensions revealed by the respondents as well as potential issues of validity, reliability and fairness of a geography assessment instrument. The implications of these findings for ongoing research are discussed.